Manage reorientation of a spacecraft with a restriction on the orientation - Шипулина, Л. В.; Татаринова, О. А.; Корытко, Ю. Н. (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The problem of the control of the space vehicle reorientation is considered in the paper with using minimal redundant gyrocomplex. The abutting spherical model in quaternion form was used for defining the control velocities of the gyrodynes precession. Graphic plots of the gyrodynes angular velocities changing is presented for minimal reorientation time.